Pengembangan pelatihan keterampilan tenis berbasis model trainer untuk atlet pemula - Aksir, Ilham; Suherman, Wawan Sundawan; Alim, Abdul; Hasmyati, Hasmyati; Mappanyukki, Andi Atssam (Universitas Nusantara PGRI Kediri, 2023)
Mastery of skills in tennis is very important to master for tennis players, especially beginner tennis players who need a lot of practice time to master the skills. Currently, tennis players only have a little time to practice, given the short duration of training with a coach. A training model that can improve beginners' mastery of tennis skills is needed. This study aimed to determine the success and effectiveness of the court tennis coach model developed for novice tennis players to improve their skills. The research method used in this study is research and development (R&D). The subjects in this study were divided into 2 stages, a small experimental stage of 15 athletes and a large trial stage of 40 athletes. The instrument in this study used a tennis dyer test. Based on the results of the assessment of sports equipment development materials, tennis coaches who are competent in their fields and sports test and measurement experts in the study